2020
DOI: 10.1186/s12955-020-01486-x
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of resilience between family functioning and mental well-being in hemodialysis patients in Japan: a cross-sectional design

Abstract: Background End-stage kidney disease is highly prevalent worldwide. Currently, one of the most effective treatment modalities is dialysis therapy, which leads to serious side effects. Furthermore, psychiatric illnesses are prevalent among dialysis patients. Recently, researchers asserted that psychological resilience and family support could be helpful to maintain or improve patients’ mental well-being. Therefore, the purpose of this study was to examine the mediating effects of resilience on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 45 publications
8
24
0
Order By: Relevance
“…Path analysis found that social support played an intermediary role in the process of SPB affecting resilience. This result was similar to those of Kukihara's research [25]. Good social support is an important line of defense for patients in overcoming the psychological burden of cancer and may result in a better quality of life [26].…”
Section: Discussionsupporting
confidence: 88%
“…Path analysis found that social support played an intermediary role in the process of SPB affecting resilience. This result was similar to those of Kukihara's research [25]. Good social support is an important line of defense for patients in overcoming the psychological burden of cancer and may result in a better quality of life [26].…”
Section: Discussionsupporting
confidence: 88%
“…Poor psychological well-being has an impact on physical health conditions (Hamdan-Mansour et al, 2015). Our study was supported by a previous study, that better family adaptability and communication resulted in greater resilience, thus it is associated with better mental health (Kukihara et al, 2020). Family support affects the quality of life (Bestari, 2016), and the health behaviors of ESRD patient receiving family support was significantly higher than before receiving family support (p < 0.01) (Shahgholian and Yousefi, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…The questions used a Likert scale with the following options: always (4), often (3), rarely (2), and never (1). The scores were combined into an index and categorized as good (49-64), sufficient (33-48), and less than sufficient (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…In one of these studies the resilience of dialysis patients was quantified with a frequently used resilience scale. They found a score of 82.4 in dialysis patients, comparable to the general population (80.4) and reasonably higher than among patients visiting a general practitioner (71.8) [21,24]. Dialysis patients may have a high level of resilience compared to primary care patients, as they have learned to adapt over time to bear the burden of dialysis and their disease in general, which could explain their ability to deal better with different stressors such as the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 90%
“…In a Spanish study, a higher level of resilience was associated with higher HRQoL scores [23]. The importance of resilience for both haemodialysis and peritoneal dialysis patients to overcome the burden of dialysis has been emphasized in multiple studies [24][25][26]. In one of these studies the resilience of dialysis patients was quantified with a frequently used resilience scale.…”
Section: Discussionmentioning
confidence: 99%